2019
DOI: 10.1017/s0954579419000221
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of callous-unemotional and oppositional defiant behaviors over a three-year interval for Spanish children

Abstract: The objective was to determine the longitudinal associations between callous-unemotional (CU) and oppositional defiant (OD) behaviors from the first to fourth grades for Spanish children. Four possible outcomes were evaluated: (a) CU behaviors in the first grade predict increases in OD behaviors in the fourth grade, controlling for OD behaviors in the first grade; (b) OD behaviors in the first grade predict increases in CU behaviors in the fourth grade, controlling for CU behaviors in the first grade; (c) both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…According to Stringaris and Goodman ( 2009 ), decomposing ODD in different dimensions can help to identify their etiological variability and may help to predict different developmental trajectories. In this line, by breaking ODD down into dimensions, reciprocal associations could be found that may not have emerged in previous cross-lagged analyses, such as Servera et al ( 2020 ), who found that higher levels of ODD at age 6 predicted more CU traits at age 9, while the reverse association was not significant and higher levels of CU traits did not predict ODD. Additionally, previous research has not adjusted for the fact that CU traits and ODD may have a common etiology, producing spurious relations between them.…”
Section: Discussionmentioning
confidence: 74%
“…According to Stringaris and Goodman ( 2009 ), decomposing ODD in different dimensions can help to identify their etiological variability and may help to predict different developmental trajectories. In this line, by breaking ODD down into dimensions, reciprocal associations could be found that may not have emerged in previous cross-lagged analyses, such as Servera et al ( 2020 ), who found that higher levels of ODD at age 6 predicted more CU traits at age 9, while the reverse association was not significant and higher levels of CU traits did not predict ODD. Additionally, previous research has not adjusted for the fact that CU traits and ODD may have a common etiology, producing spurious relations between them.…”
Section: Discussionmentioning
confidence: 74%